Appraisal of 100% school transition in Kenya: challenges and policy options - Njeru, A. M. (Strathmore University, 2025)
This study draws important lessons from international best practices to inform Kenya’s 100% school transition policy. Key models include Rwanda’s needs-based funding mechanism, Saudi Arabia’s Public-Private Partnerships (PPPs) for infrastructure expansion, New Zealand’s ICT-driven education monitoring system, and Brazil’s integration of technology in learning. These cases provide actionable insights for improving policy implementation, equity, and sustainability in Kenya’s context. The study was guided by three main objectives: to assess the key factors hindering 100 percent school transition in Kenya; to appraise the transition policy by identifying issues emerging from its implementation; and to draw lessons from international best practices to inform policy improvement. A descriptive qualitative research design was adopted to enable in-depth exploration of stakeholder experiences and policy dynamics. Using purposive sampling, 30 participants were selected from across Kenya’s former eight administrative regions. Data was collected through semi-structured interviews and analyzed thematically to identify patterns, trends, and policy gaps. Findings reveal that the effectiveness of Kenya’s transition policy is undermined by weak implementation frameworks, including the absence of a structured student tracking system and delays in financial disbursements. Governance challenges, high student-teacher ratios, inadequate professional development, and inequitable deployment of teachers further exacerbate the problem. Additionally, external environmental and socio-economic factors—such as insecurity, climate disruptions, and poverty—disproportionately impact vulnerable communities, making full transition difficult to achieve. The study concludes that while the 100% transition policy reflects a commendable commitment to universal secondary education, its long-term success depends on strategic reforms. These include implementing a real-time education data system, adopting a data-driven teacher deployment strategy with rural incentives, and expanding infrastructure through innovative financing mechanisms like PPPs. Without such reforms, the policy risks becoming a numerical success with limited educational quality or equity.
Full - text thesis